Business Environment Reform in MENA : Setting Up the Right Implementation Framework - de Meneval, Philippe; Saadani, Youssef (World Bank, Washington, DC, 2012)
In many developing countries numerous ambitious reform agendas have faltered and failed to have significant impact on the ground, often creating a counterproductive 'reform fatigue'. Most governments have at their disposal detailed assessments of their investment climate and are able to identify weaknesses. However, expert diagnostics and political will alone are not enough to succeed in reforming the investment climate. Reform initiatives often get bogged down because of a lack of institutionalized inter-ministerial coordination, open public-private dialogue, and efficient project management. Best reformers worldwide have taken into account this implementation challenge. Recent studies have demonstrated that, in addition to establishing a performing high-level decision-making body, these countries have developed a full-fledged reform process that includes a dedicated reform team at the center of government and a structured dialogue mechanism with the private sector to better coordinate reform identification and implementation. As highlighted in the 2008 report of the commission on growth and development: 'making policy is only part of the battle. Policies must also be faithfully implemented and tolerably administered.'